Development and Characterization of PLA Composites with High Contents of a Brazilian Refractory Clay and Improved Fire Performance - Rabelo,Letícia Heldt (2022)
Abstract Aiming to overcome poly(lactic acid) (PLA) limitations regarding flammability and high costs, a highly refractory clay (RC) was employed to produce PLA/RC composites. The composites with clay contents of 0, 2.5, 10 and 15 wt% were produced by extrusion, conformed by injection molding, and characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), mechanical analysis, scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), statistical analysis of variance (ANOVA) and flammability tests. The overall thermal stability of the materials was not affected by the incorporation of clay to the polymer matrix; improvements around 25% for Young’s modulus and slight increase in flexural and impact strength, when compared to neat PLA, were obtained; ANOVA showed the possibility of incorporating higher loads of clay, 10-15 wt%, in order to make the final material more cost effective. PLA/RC composites demonstrated self-extinguish behavior for the flame even at a lower clay content.